Higher risk of recurrence in partially thrombosed cerebral aneurysms post-WEB (Woven EndoBridge) device treatment: insights from the WorldWideWEB Consortium registry - Saliou, Guillaume; Salim, Hamza Adel; Musmar, Basel; Adeeb, Nimer; Aslan, Assala; Swaid, Christian; Cuellar, Miguel; Dibas, Mahmoud; Cancelliere, Nicole M; Diestro, Jose Danilo Bengzon; Algin, Oktay; Ghozy, Sherief; et al. (Journal of neuroInterventional surgery, 2025)
Background - The Woven EndoBridge (WEB) device is a prevalent treatment for intracranial aneurysms. While many studies have assessed the obliteration rate post-WEB embolization, few have focused on long-term outcomes in partially thrombosed aneurysms. - - - Objective - To assess whether partially thrombosed aneurysms are at higher risk of recurrence or retreatment following WEB embolization compared with non-thrombosed aneurysms. - - - Methods - We evaluated data from 22 academic institutions, focusing on previously untreated cerebral aneurysms treated with the WEB device. Logistic regression was utilized to analyze factors predicting long-term aneurysm obliteration and retreatment necessity. - - - Results - Among 1303 patients, 26 presented with a partially thrombosed aneurysm. In the partially thrombosed group, the mean aneurysm maximal diameter was 10.7±4 mm with a neck ratio of 1.99±1.19 mm, larger than in the control group where the mean aneurysm maximal diameter was 6.81±2.37 mm with a neck ratio of 1.64±0.51 mm (P<0.001 for both maximal diameter and neck ratio). At the final follow-up, partially thrombosed aneurysms treated by the WEB device had a 38.5% retreatment rate, compared with 7.0% for non-thrombosed aneurysms (P<0.001). Among partially thrombosed aneurysms, the Raymond-Roy type IIIa/b occlusion rate was higher (38.5% vs 9.9%, P<0.001). On multivariate analysis, partially thrombosed aneurysms compared with non-thrombosed aneurysms had an increased rate of retreatment (OR 3.64, 95% CI 1.28 to 10.1). - - - Conclusion - Partially thrombosed aneurysms are associated with a poorer occlusion rate and a higher rate of retreatment following WEB embolization. For partially thrombosed aneurysms, the WEB device appears suboptimal as a first-line treatment, and therefore alternative techniques should be prioritized.
Gesehen am 03.11.2025